Governance and Regulation of Power Pools and System Operators : An International Comparison. - Barker, Jame; Tenenbaum, Bernard; Woolf, Fiona (Washington: World Bank Publications, 1997)
Annotation
Annotation
Scholarly & Professional
Keywords: World Bank